Ligand Binding to the Membrane-Distal Domain of the Met Receptor Induces Dimerization at the Membrane-Proximal Domain - Neval Yilmaz (1544557) (2025)
Activation of cytokine and growth factor receptors by ligands triggers crucial cellular responses in various physiological processes. However, our understanding of their structural basis remains incomplete due to the limited information on the active ligand–receptor complex structure. Their structural analysis poses two significant challenges: preserving the complex structure during isolation from living cells and achieving high-resolution characterization. In this study, we analyzed the structure of the active complex of the hepatocyte growth factor (HGF)-Met receptor by chemically fixing prior to isolating from living cells and high-speed atomic force microscopy imaging at the single-protein level. We also conducted split-luciferase complementary assay and cryo-electron microscopy experiments for the HGF-Met extracellular domain complex and complemented these results with molecular dynamics simulations. We found that HGF binding to the Sema domain of Met promotes homotypic dimerization at the membrane-proximal region of Met, specifically the IPT4 domain. In summary, our study unveils the structural features of the physiological HGF-Met complex and clarifies the ligand-induced dimerization of the Met receptor.